La mémoire du risque à Mayotte, un atout pour la prévention des risques naturels ? - Mathilde Rullier; Gilles Hubert (EchoGéo)
In a global context of climate change, Mayotte, an insular territory in the Indian Ocean and a recent French overseas department and region (DROM), sees its population highly exposed to multiple natural risks. However, the territory has to face up to a number of challenges while responding to emergencies. The territory's natural risks management policy is based on national and European frameworks, but the risk culture is being built up locally. Despite past significant meteorological events, high migratory flows and a context radically different from that of the French mainland, the memory of the inhabitants can prove to be an asset that can be mobilized to anchor a localized risk culture adapted to today's challenges.